PENERAPAN PROBLEM BASED LEARNING TERHADAP KETERAMPILAN BERPIKIR KERITIS DAN HASIL BELAJAR SISWA MA NURUL HIKMAH MURANGSANAH KOKOP BANGKALAN - Arofah, Abd. Rahman; Widayat, Edy; Sarmi, Ni Nyoman (Jurnal Ilmiah Wahana Pendidikan, 2024)
The aim of the research is to determine the differences in critical thinking skills and differences in learning outcomes with the application of PBL (Problem Based Learning) and conventional students at MA Nurul Hikmah Murangsanah Kokop Bangkalan. Quantitative approach, the method used for data collection and data analysis. The type of experimental research with a design is quasi-experimental in the form of a pretest-posttest control group design. The results of data calculations obtained an average score for the experimental class of 83.5, with a total of 30 students using the problem based learning model. 23 students, student learning outcomes in control class X-A and experimental class X-B, from the average score of control class X-A and experimental class obtained from the final test after learning ended, while the student learning outcomes in the X-B experimental class were obtained at 79.33 from the results of the final test conducted by researchers after learning, so it appears that the influence of the problem based learning model was 40.4% on student learning outcomes in MA Nurul Hikmah Murangsanah Kokop Bangkalan.